Analisis Kausalitas Keputusan Investasi, Pembiayaan dan Dividen pada Perusahaan Asuransi - Sutrisno Sutrisno; Yuana Yuana (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2004)
The study aims at analyzing the causal relationship of decision-making concerning investment, financ¬ing from retained earning and dividend of insurance corporations at Jakarta Stock Exchange. The rationale of choosing this subject because of unique factor from industry and the tendency of insurance industries as a large business, which reach the world in the future.Result of this research is expected to give input for Insurance Corporations Management to be wiser in determining the investment of decision making, financing from retained earning and dividend, especially in divi¬dend payment and the hold profit increasing in financing patterns.The research result on the causality among the tree variables indicates that insurance corporations in Jakarta Stock Exchange are within the fist theory Miller and Modigliani he said the decision of dividend no influ¬ence to value of corporation and also capital expense. The causality between decision-making concerning in¬vestment, financing from retained earning and dividend is not always absolute for the research made on homogen markets relatively.